Police, provocation, politics: counterinsurgency in Istanbul - Yonucu, Deniz (Police/worlds studies in security, crime, and governance, 2022)
"Situating Turkish counterinsurgent policing within a global context of Cold War counterinsurgencies that inform current security practices and combining archival work and oral history with ethnographic research in Istanbul's dissident working-class neighborhoods, the book sheds light on counterinsurgency's provocative, affect generating, divisive techniques and urban dimensions"--